Screening of tuberculosis suspected subjects using real-time PCR, TaqMan method; Northeastern Iran - Ahmadi Ghezeldasht, Sanaz; Mosavat, Arman; Soleimanpour, Saman; Rezaee, Seyed Abdolrahim; Derakhshan, Mohammad (Journal of infection and public health, 2025)
Effective and timely tuberculosis (TB) treatment depends on rapid reliable diagnostic techniques and is crucial for controlling global TB. The present study aimed to determine how many TB presumptive patients may have been missed by conventional sputum smear microscopy and culture methods. This cross-sectional study was conducted from 2020 to 2021 in northeast Iran. A total of 307 TB presumptive subjects with negative Ziehl-Neelsen (ZN) staining microscopy, and culture tests were evaluated using a lab made real-time PCR (qPCR), TaqMan method. The control group was 21 M. tuberculosis (M.tb) positive subjects from a referral TB center; Northeastern Iran. All cases in TB-positive control group tested positive by qPCR. Out of the 307 negative culture and smear tests individuals, 50 (13.55 %) tested positive using qPCR. Failure rates for microscopy and culture were higher in urine samples; none were positive in smear and culture tests, but six out of 20 (30 %) were qPCR positive. Lower failure rates for conventional tests were observed in sputum samples, with 18 out of 53, and qPCR detected nine more cases. Furthermore, among 61 unculturable samples, one case was positive using qPCR technique. Overall, qPCR demonstrated a 100 % and 83.7 % sensitivity and specificity, respectively. In-house qPCR assays using standard reagents, which are generally available can confirm that this method more practical, time-saving, and feasible for TB-suspected individuals, particularly in extrapulmonary forms such as urine, CSF, and paraffin-embedded samples, compared to direct microscopy and culture.